KONSEP SEMIOTIK CHARLES JENCKS DALAM ARSITEKTUR POST- MODERN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
The aims of this research ..are to know and to explain Charles Jencks' semiotic concept of postmodem architecture. In one hand, Jencks' postmodem architecture is criticism on modem and modem-late architecture. Jencks stresses on differences that modem and modern-late architecture are based on a single coding only, and postmodem architecture is based on double coding in their style. In other one, Jencks' postmodern architecture is a semiotic.entity that has to seen as a sign. This research is the figure factual history research. It is based on primary and secondary literatures. It uses description, interpretation and heuristic method. Jencks's semiotic. conception of postmodem architecture has adopted dualism semiotic of Saussuran like signifier-signified, langue-parole, denotation-connotation, and paradigmatic-sintagmaticoIt also .hasadopted trilateral semiotic of Piercean like index, icon, symbol and sintagmatic, syntactic, semantic.